Intermediate Algebra (12th Edition)

Published by Pearson
ISBN 10: 0321969359
ISBN 13: 978-0-32196-935-4

Chapter 4 - Section 4.4 - Multiplying Polynomials - 4.4 Exercises: 44

Answer

$6m^{2}+7mn-5n^{2}$

Work Step by Step

We are given the expression $(2m-n)(3m+5n)$. We can find the product of this expression using the FOIL method. First terms: $2m\times 3m=6m^{2}$ Outer terms: $2m\times5n=10mn$ Inner terms: $-n\times 3m=-3mn$ Last terms: $-n\times5n=-5n^{2}$ Adding together: $6m^{2}+10mn+(-3mn)+(-5n^{2})=6m^{2}+10mn-3mn-5n^{2}=6m^{2}+7mn-5n^{2}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.